SDN Based Data Offloading and Load Balancing Techniques for Applications in 5G - V, Shilpa; Ranjan, Rajeev (International journal of recent technology and engineering, 2019)
a huge development of wireless users traffic and the deficiency of accessible resources has led to new difficulties for future cell systems. Nowadays our network needs to deal with extensive measure of traffic and serve a large number of customers. It is exceptionally difficult for a solitary server to deal with such tremendous burden. Since, the architecture of 5G is highly advanced by using SDN and NFV, its network elements and various terminals are characteristically upgraded to afford a new solution for these traffic issue. In this paper we proposes a data offloading algorithm by forwarding the traffic between cellular network, femtocell and Wi-Fi network in order to reduce the overall burden on cellular network. We also proposes a load balancing technique which will manages the available network resources between the incoming user requests and existing users. The proposed traffic offloading algorithm uses an SDN controller for i) making the decisions of forwarding data between femtocell network, Wi-Fi and cellular network. ii) it also uses controller for taking the decisions in balancing the load of users with the existing the resources.